Crisis and arbitrage opportunities: The role of causation, effectuation and entrepreneurial learning. (March 2022) - Khurana, Indu; Dutta, Dev K; Schenkel, Mark T
This article examines the process by which entrepreneurs identify and work with an arbitrage opportunity emerging from an episodic crisis. Although prior research has investigated the role of entrepreneurial characteristics and context on opportunity development, the specific manner in which these factors emerge in the course of opportunity development during a crisis remain underexplored. By adopting a qualitative approach grounded in case studies of eight entrepreneurs in the US distillery industry, this article addresses that gap by examining the process of arbitrage opportunity development during COVID-19. Our study reveals the primacy of both causation and effectuation-based entrepreneurial decision logics and the role of double-loop learning, as entrepreneurs interact with the time-compressed duration of the arbitrage opportunity. Implications and insights for entrepreneurs, researchers and policymakers are discussed.